Design and simulation of micro-filter for particle concentration - Bey, Wee Yong (2019)
Microfilter is a device used for Microfiltration, a common separation technique for removing micron-sized particles. It has a wide range of applications such as Water treatment and remove micro-emboli from blood. In Singapore, Microfiltration is a crucial step in used water treatment to produce NEWater, which aims to meet the water demand in future. Microfilter is designed with different pore sizes, pore shape, pitch distance and membrane material for different applications. It is time-consuming to do the calculations behind to design microfilters for different purpose, due to the complexity involved in the design processes of the microfilter. Currently, commercial software like Ansys and COMSOL can simulate the MF membrane. However, the cost for the license can be up to several hundred Singapore dollars. More studies on Microfilter should be done to optimise its purpose to save time and cost of designing Microfilter. More studies on Microfilter should be done to optimise its purpose to save time and cost of designing Microfilter. An in-house developed model will be free of charge for those with limited budget. This project aims to implement a set of algorithms and develop an in-house design tool to guide and optimise membrane performance for MF applications in future studies and research. This is done by analysing the relationship between water flow rate and the stress acting on MF membrane during the filtration process. The implementation of algorithm is done with MATLAB and designed to aid future similar studies in reducing the time on calculations. Two models, Model 1 and Model 2, are used to simulate the correlation between flowrate, transmembrane pressure and stress can speed up the microfilter design process. The relationship between water flowrate and the stress acting on MF membrane during the filtration process is analysed with 5 types of MF membrane with different pore size and distance between the pores. The results show that Model 2 is more applicable in analysing the 5 types of MF membrane by producing stress values that is within an acceptable range for small pores size. As the flowrate through the membrane increases, the maximum stress and deflection also increases. The Transmembrane pressure, maximum stress and deflection increase as the pore size of the membrane decrease at a fixed flowrate. Commercial software COMSOL is used to cross validate result of the MATLAB to ensure the in-house tool is usable with an accuracy of 84%. The implementation of this in-house tool is useful and helps to save time consuming Microfilter design and simulation process from several hours to minutes.